1938
DOI: 10.1084/jem.67.3.345
|View full text |Cite
|
Sign up to set email alerts
|

Blood Plasma Proteins as Influenced by Intravenous Injection of Gum Acacia

Abstract: Any experimental technique which involves disturbance of liver function is of particular interest in regard to plasma protein studies, for there is evidence that the liver is associated in the production of plasma protein. When a solution of gum acacia is injected intravenously in the dog, there is a marked decrease in the blood plasma protein concentration (5). That the liver is concerned with this process is suggested by the observation that injected gum acacia is rapidly removed from the blood and deposited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1938
1938
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…During the periods of injection, except when otherwise indicated, weekly determinations of total plasma protein, fibrinogen, albumin, and globulin were made in all cases by methods described in a previous publication (6). Plasma volume determinations were made by a modification of the method of Gibson and Evans (5) using T-1824 dye.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…During the periods of injection, except when otherwise indicated, weekly determinations of total plasma protein, fibrinogen, albumin, and globulin were made in all cases by methods described in a previous publication (6). Plasma volume determinations were made by a modification of the method of Gibson and Evans (5) using T-1824 dye.…”
Section: Methodsmentioning
confidence: 99%
“…The mechanism of the interrelationship of injected gum acacia and plasma protein in the blood stream involves principles which may lead to a better understanding of plasma protein both as to its production and its function as a blood colloid. In dogs, following single, or a few repeated injections of gum acacia, there are profound changes in plasma protein and fibrinogen concentration and in total circulating plasma protein (6). Since it has not been possible to account for the loss of protein from the blood stream by an increase of nitrogen in the urine, it has been suggested that the missing plasma protein has been replaced (or displaced) by acacia and deposited in "storage depots" in the body.…”
mentioning
confidence: 99%
“…A related solution was implemented at forward camps during the final months of World War I, thus marking the first widespread use of resuscitation with colloids [23]. Ultimately, the adoption of gelatin was delayed owing to issues with preparation and storage, and gum arabic was abandoned secondary to its hepatotoxicity and antigenicity [24,25]. The first commercially produced synthetic colloidal resuscitation solution polyvinylpyrrolidon was synthesized by the prolific German chemist Walter Reppe in 1939 and later marketed by Bayer under the trade name Periston [26].…”
Section: Historical Perspectives On the Debate And Colloid Developmentmentioning
confidence: 99%
“…The important question of the formation of serum proteins has been the subject of a number of investigations. Among these, the extensive studies of Whipple and his collaborators (1)(2)(3)(4) should be mentioned especially. The authors brought evidence to show that the liver plays an important part in the production of plasma proteins, in particular albumin.…”
mentioning
confidence: 99%